A Power-Aware Broadcasting Algorithm - Miranda, Hugo (2009)
Flooding is an expensive but unavoidable operation in some application scenarios devised for Mobile Ad Hoc Networks (MANETs). In this paper, we present a novel algorithm to reduce the overhead imposed by flooding operations. The algorithm improves previous results by using a distributed function to elect the nodes that will provide the highest additional coverage to previous retransmissions. The algorithm does not require any signalling or imposes special requirements on the participating devices.